1996
DOI: 10.1111/j.1600-0838.1996.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

The sportsman's hernia ‐ fact or fiction?

Abstract: This review is based on the results of 308 operations for unexplained, chronic groin pain suspected to be caused by an imminent, but not demonstrable, inguinal hernia: the 'sportsman's hernia' (SH). No differences in perioperative findings between cured and non-cured athletes were found. However, there was a remarkable difference between the various perioperative findings in the studies. It was characteristic that further clinical investigation of the noncured, operated athletes gave an alternative and treatab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 13 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…All of these structures have been suggested as potential sites of failure in groin pain in athletes, and since, it is also believed that multiple structures are commonly affected, clinical sensitivity is further decreased 2 4. Some authors believe inguinal aponeurotic injury initiates the process leading to symphyseal, rectus abdominis and adductor change developing later while others believe the process occurs in reverse 5–7…”
Section: Introductionmentioning
confidence: 99%
“…All of these structures have been suggested as potential sites of failure in groin pain in athletes, and since, it is also believed that multiple structures are commonly affected, clinical sensitivity is further decreased 2 4. Some authors believe inguinal aponeurotic injury initiates the process leading to symphyseal, rectus abdominis and adductor change developing later while others believe the process occurs in reverse 5–7…”
Section: Introductionmentioning
confidence: 99%
“…Geographical and sports-specific differences seem to exist for the overdiagnosis or underdiagnosis of a sports hernia, with European soccer players with chronic groin pain more often diagnosed with a sports hernia and Australian Rules Football players with chronic with chronic groin pain more often diagnosed with osteitis pubis 22 24 – 26. Fredberg et al 27 suggested that proper evidence does not exist for the theory that a sports hernia constitutes a credible explanation for chronic groin pain, calling for greater restraint before surgical intervention.…”
mentioning
confidence: 99%
“…Our definitions of the three extra-articular causes of athletic groin pain are (1) adductor dysfunction, which is considered to be present if the physical examination demonstrates tenderness at the adductor enthesis as well as pain on passive adductor stretching and on resisted adduction; (2) osteitis pubis, which is inflammation of the pubic symphysis manifesting as a tender symphysis and which can be identified on magnetic resonance imaging; and (3) sports hernia, which is a clinical diagnosis confirmed at surgery and consists of any combination of a torn external oblique aponeurosis, a torn conjoined tendon, and dehiscence between the conjoined tendon and the inguinal ligament [1][2][3][4] (Table I).…”
mentioning
confidence: 99%